Influência da quantidade de matriz extracelular na atividade antifúngica de nanopartículas de prata contra biofilmes de espécies de Candida - Feresin, Leonardo Perina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of the present study was to evaluate the influence of the amont of extracellular matrix on the antifungal activity of silver nanoparticles (SN) against single and mixed biofilms of Candida albicans and Candida glabrata. SN were synthesized by silver nitrate reduction with sodium citrate and stabilized with ammonia. Single and mixed biofilms of Candida species were formed (48 hours) under agitation of 10 and 120 rpm to form lower and higher amounts of extracellular matrix, respectively on the surfaces of acrylic resin specimens inside 24-wells microtiter plates. Then, biofilms were exposed to different concentrations of SN (54 and 108 μg/mL) for 24 h. Chlorhexidine digluconate (CHG) in a concentration of 108 μg/mL was used as positive control. After the treatment period, biofilms were assessed by total biomass quantification (by crystal violet staining) and colony forming units (CFU) enumeration. The structure of Candida biofilms was analyzed by scanning electron microscopy (SEM) images. The results indicated that the amount of extracellular matrix affected the antifungal activity of SN in decreasing total biomass of single and mixed biofilms of oral clinical isolates, with higer reductions for those formed at 10 rpm. Interestingly, the comparisons of different incubation conditions (10 and 120 rpm) at the same SN concentration showed statistical difference (p < 0.05) in the number of CFUs only to reference strain of C. albicans in mixed biofilms treated with SN at 54 μg/mL. By SEM, Candida biofilms treated with SN and CHG revealed structural differences, when compared to the negative control groups. In general, the amount of extracellular matrix affected differently the total biomass and the number of cultivable cells of Candida biofilms. Moreover, given the antifungal effect of SN in decreasing total biomass and number of CFUs...

O objetivo do presente estudo foi avaliar a influência da quantidade de matriz extracelular na atividade antifúngica de nanopartículas de prata (NPs) contra biofilmes simples e mistos de Candida albicans e Candida glabrata. NPs foram sintetizadas através da redução do nitrato de prata pelo citrato de sódio e estabilizadas com amônia. Biofilmes simples e mistos das espécies de Candida foram formados (48 horas) sob agitação de 10 120 rpm (para formar menor e maior quantidade de matriz,respectivamente, sobre a superfície de espécimes de resina acrílica posicionados no interior de placas de microtitulação de 24 poços. Na sequência, os biofilmes foram tratados por 24 horas com NPs nas concentrações de 54 e 108 μg/mL.O digluconato de clorexidina (DC) na concentração de 108 μg/mL foi usado como controle positivo. Após o período de tratamento, os biofilmes foram avaliados por meio da quantificação da biomassa total (usando a coloração de cristal violeta) e das unidades formadoras de colônias (UFCs). Ainda, a estrutura dos biofilmes de Candida foi analisada por meio de imagens de microscopia eletrônica de varredura (MEV). Os resultados indicaram que a quantidade de matriz extracelular afetou a atividade antifúngica de NPs na redução da biomassa total de biofilmes simples e mistos dos isolados clínicos orais, com maiores reduções para os biofilmes formados sob agitação de 10 rpm. Por outro lado, comparando as diferentes condições de incubação (10 e 120 rpm) para uma mesma concentração de NPs, foi possível notar diferença significante (p < 0,05) no número de UFCs somente para a cepa referência de C. albicans em biofilme misto tratado com NPs a 54 μg/mL. Por meio das imagens de MEV, os biofilmes tratados com NPs e DC apresentaram diferenças estruturais quando comparados aos seus respectivos controles. Portanto, no...
Keywords: Candidíase bucal; Biofilmes; Candida; Candidiasis, Oral